2014
DOI: 10.4028/www.scientific.net/amm.592-594.1801
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on the Application of Pulsating Heat Pipe in Vapour Compression Refrigeration System

Abstract: This paper proposes a simplified theoretical model of Pulsating Heat Pipe (PHP) employed in a vapour compression refrigeration system. The model developed is mainly based on well known physical equations and partially based on empirical correlation. The present theoretical investigation of PHP is focused to explore its suitability as a heat exchanger in the condenser of vapour compression refrigeration system. A parametric analysis is carried out to design the vapour compression refrigeration system with PHP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The cooling capacity of the condensation section of PHP is also very important among many factors and has attracted the attention of many scholars in recent years. Naik et al [16] put forward a simplified theoretical model of PHP used in the vapor compression refrigeration system. It was found that the performance of the system was improved at a higher temperature of the evaporation section and a lower temperature of the condensation section.…”
Section: Introductionmentioning
confidence: 99%
“…The cooling capacity of the condensation section of PHP is also very important among many factors and has attracted the attention of many scholars in recent years. Naik et al [16] put forward a simplified theoretical model of PHP used in the vapor compression refrigeration system. It was found that the performance of the system was improved at a higher temperature of the evaporation section and a lower temperature of the condensation section.…”
Section: Introductionmentioning
confidence: 99%
“…A simplified theoretical model of PHP employed as the condenser in a vapor compression refrigeration system has been developed. The performance of the system was improved [18]. PHP had also been used as heat sink of a high power LED street light [19] and defrosting plate [20].…”
Section: Introductionmentioning
confidence: 99%